Effect of acupuncture TENS versus conventional TENS on post cesarean section incision pain - Mehendale, Priti A.; Revadkar, Mayur T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: There is evidence regarding beneficial use of Transcutaneous Electrical Nerve Stimulation (TENS) on post Lower Segment Caesarean Section (LSCS) incision pain. However, efficacy of different types of TENS following C section pain has not yet been explored adequately. Methods: 96 women who had recently undergone LSCS were included for the study. The subjects were in the age group of 20 to 40 years (25.84±3.96); having pain intensity 4 or more on Numerical Pain Rating Scale (NPRS). They were divided into three groups by random allocation method; namely Group A: Acupuncture (Low/Motor) TENS, Group B: Conventional (High/Sensory) TENS and Group C: Control group. Group A and B received specific type of TENS twice a day for 15 minutes. Control group C did not receive any TENS intervention. All subjects received standard post-operative medications and physiotherapy. Pain intensity was recorded on NPRS pre and post intervention. Results: Both Acupuncture TENS and Conventional TENS significantly decreased post-operative pain intensity as compared to control group (p value <0.0001). Conclusions: Both, acupuncture and conventional TENS are equally effective in reducing post LSCS incision pain at a strong and non-painful intensity.